NONESSENTIAL PQ-INJECTIVE MODULES - Wongwai, S.; Thiangtong, N.; Pimonlsith, V.; Pornpunpaibool, P. (IJRDO -JOURNAL OF MATHEMATICS, 2017)
Let M be a right R − module. A right R − module N is called nonessentialprincipally M - injective (briefly, nonessential PM - injective) if, for each s S ∈ with e s(M) M, ⊄ any R − homomorphism from s(M) to N can be extended to an R − homomorphism from M to N. M is called nonessential principally quasi- injective (briefly, nonessential PQ - injective) if, it is nonessential PM - injective. In this paper, we give some characterizations and properties of nonessential PQ - injective modules